Switzerland : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Switzerland during 1990-95. In the early 1990s, Switzerland experienced an unusually long recession, which bottomed out in the middle of 1993. Since then, the economy has returned to positive growth, with the main impulses coming from commodity exports and private investment. There was renewed growth in gross capital formation of close to 6 percent in 1994, reflecting improved business confidence deriving mainly from growing export orders. Investment in machinery and equipment, in particular, was the sole component of domestic demand to grow strongly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet